The Effect of Physiotherapy Education on Parents on Reducing Spasticity in Children of The Spastic Type of Cerebral Palsy - Hidayati, Nitaya Putri Nur; Triyana, Triyana; Noerdjanah, Noerdjanah (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Cerebral Palsy is a group of children with movement and posture development disorders caused by brain nerve damage. The development of children with Cerebral Palsy is influenced by the role of parents in caring for and raising them daily. This ability must be based on good and specific knowledge and skills, because cerebral palsy children have many problems and disorders, both from physical, psychological, and social aspects. This knowledge and skills can be obtained from professional health workers. Objective: To determine the effect of physiotherapy education for parents on reducing spasticity in children with spastic type of cerebral palsy. Methods: This is an experimental research with one group pre and post-test design with control which was carried out on parents of children with cerebral palsy at the Forum Buah Hati. Results: The difference test between before and after providing physiotherapy education, obtained a value of p=0.157. Meanwhile, the analysis using different means for each group received a difference in the Modified Ashworth Scale (MAS) value in the treatment group of 0.33 and the control group of 0.17. Conclusion: There is a less significant effect of providing parental education on reducing spasticity in spastic-type Cerebral Palsy children.